Alterations of constitutive pericentromeric heterochromatin in lymphocytes of cancer patients and lymphocytes exposed to 5-azacytidine is associated with DNA-hypomethylation - Shvachko, L.P. (Experimental Oncology, 2008)
DNA hypomethylation plays a key role in carcinogenesis. The malignant transformation of cells as well as tumor progression is accompanied with increasing DNA hypomethylation in cancer cells. Nevertheless, the evolution of dis-epigenetic genomic alteration in the somatic cellular malignant transformation has not yet been clear. Aim: To study the relationship between the pattern of genomic DNA hypomethylation and DNA hyperploidy. Methods: The model of 5-azacytidine demethylating DNA treatment of the mitogen-stimulated lymphocytes in parallel with patients with solid cancer has been explored. DNA content was measured by quantitative DAPI and Hoechst 33258 fluorescence in situ hybridization on interphase nuclei. The conventional mitogen-stimulated blood lymphocyte culture development was performed in metaphase chromosomes and interphase nuclei assay. The light and fluorescent cytomorphological microscopy was performed. Results: The model 5-azacytidine induced DNA demethylation results in increased DNA hyperploidy accompanying major pericentromeric heterochromatin (Alu) DNA repeats amplification similar to those during DNA hypomethylation-associated cancer events, and both contributed to nuclear heteropycnosis development. The constitutive pericentromeric heterochromatin consequent morphological disturbance to the latent polytene chromomerization and heteropycnosis development both in cancer patients and in model 5-azacytidine exposured lymphocytes are associated whith DNA hypomethylation. Conclusion: We have observed that the induced global DNA hypomethylation triggers dis-epigenetic morphological reprogramming of constitutive pericentromeric heterochromatin on the extrachromosomal organization pathway as seen during the heterochromatin latent polytene features development, which is of importance as one of the mechanism involving DNA hypomethylation in initiation and progression of cancer. ДНК-гипометилирование играет ключевую роль в канцерогенезе. Маллигнизация, как и прогрессия опухоли, сопровождается увеличением гипометилирования ДНК в опухолевых клетках. Тем не менее до сих пор вопросы эволюции дис-эпигенетических геномных изменений в соматической клеточной злокачественной трансформации, связанной с ДНК-гипометилированием, остаются невыясненными. Цель: исследовать взаимоотношения между характером геномного ДНК-гипометилирования и ДНК-гиперплоидностью. Методы: в модельной системе ДНК-деметилирования 5-азацитидином обрабатывали митогенстимулированные лимфоциты и лимфоциты периферической крови онкобольных с солидными опухолями. Содержание ДНК определялось на основе количественной DAPI и Hoechst 33258 флуоресценции интерфазных лимфоцитов. Фитогемагглютининстимулированная культура лимфоцитов использовалась для исследования метафазных хромосом и интерфазных ядер с помощью световой и флуоресцентной микроскопии. Результаты: модельное действие 5-азацитидина увеличивает соматическую ДНК-гиперплоидность, которая сопровождается направленной амплификацией основных перицентромерных Alu ДНК-повторов, подобно таковой при онкологическом процессе, ассоциированном с геномным гипометилированием, что вносит вклад в развитие ядерного гетеропикноза. Выводы: выявлено, что индуцированное глобальное гипометилирование ДНК запускает дис-эпигенетическое репрограммирование конститутивного перицентромерного гетерохроматина по пути экстрахромосомной организации, как показано в развитии латентной политении гетерохроматина, которая является одним из ключевых механизмов вовлечения гипометилирования в инициацию развития и прогрессию опухолей.